Experimental and theoretical studies on a novel of a [3,2-?]pyrimidine derivate - Acar, Betul; Caliskan, Nezihe; Cukurovali, Alaaddin (Int Union Crystallography, 2013)
[Abstract Not Available]
Keywords: X-ray; ab-initio calculations